A Framework for Patient Practitioner Information Exchange - Forbes, David; Sidhu, Amandeep; Singh, Jaipal (IEEE, 2010)
The global Type 2 Diabetes Mellitus (T2DM) epidemic imposes a heavy burden on communities that are ethnically vulnerable to the disease and further disadvantaged by socio-economic circumstance and cultural communications barriers. Aboriginal communities in rural and remote Western Australia are representative of these high-riskgroups. Indigenous patients needing continuous management of T2DM are also experiencing disproportionate risk of co-morbidities and hospitalizations compared with nonindigenous patients. Type 2 Diabetes Mellitus (T2DM) is often described as ’the lifestyle disease’. Within clinical care and patient quality of life management domains, T2DM presents both the healthcare practitioner and the patient with a mosaic of complexities.Information processing demands for self-management of diabetes are extensive, requiring constant self monitoring and assessment of the illness state in order to apply per instance and per condition the most appropriate form of control. In this work we introduce a primary care communications concept tool centered upon optimization of the Patient-Practitioner Interview Encounter (PPIE). The target beneficiary is the Aboriginal T2DM patient living in Western Australia. Avital part of our design effort is therefore dedicated to understanding and responding to the cultural domain barriers, challenges and opportunities of this specific health care environment.